APPROACHES TO UNDERSTANDING THE PHENOMENON OF POLYSEMY (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article provides an overview of approaches to understanding the phenomenon of polysemy, and considers the issue of interpretation of the concept of lexical-semantic variant and its relationship with the concept of “meaning”. The possibilities of an invariant approach to organizing the meaning of a word are analyzed.